Single-molecule magnet behavior in a CuII-decorated DyIII2 complex with nitronyl nitroxide biradicals. Issue 8 (9th February 2018) - Li, Hongdao; Sun, Zan; Sun, Juan; Xi, Lu; Guo, Jianni; Sun, Guifang; Xie, Jing; Ma, Yue; Li, Licun
Abstract : Unprecedented octa-spin-center 2p–3d–4f compounds were obtained using a specially designed nitronyl nitroxide biradical, where the Dy analogue exhibited SMM behavior. Abstract : Herein, based on a novel nitronyl nitroxide biradical ligand NITPhPyoebis (1 ) (5-(4-pyridinone)-1, 3-bis(1′-oxyl-3′-oxido-4′, 4′, 5′, 5′-tetramethyl-4, 5-hydro-1 H -imidazol-2-yl)benzene), four 3d–4f heterometallic polynuclear compounds, namely [Ln2 Cu2 (hfac)10 (NITPhOPybis)2 ] (Ln III = Gd2, Tb3, Dy4 and Ho5 ; hfac = hexafluoroacetylacetonate; NITPhOPybis = 5-(4-oxypyridinium-1-yl)-1, 3-bis(1′-oxyl-3′-oxido-4′, 4′, 5′, 5′-tetramethyl-4, 5-hydro-1 H -imidazol-2-yl)benzene) were synthesized successfully. In these 3d–4f compounds, two NITPhOPybis biradical ligands acted as bridge ligands with the μ3 -η 1 :η 2 coordination mode to bind two Ln III ions and two Cu II ions, generating octa-spin 2p–3d–4f systems. Strong antiferromagnetic coupling was observed between the Cu II ion and the coordinated NO group while there is weak antiferromagnetic interaction between the two Gd III ions bridged by double oxygen atoms. The frequency-dependent out-of-phase signals associated with the slow relaxation of magnetization confirm the single-molecule magnet behavior of the Dy complex.